Recent Progress in Magnetically Actuated Microrobots for Targeted Delivery of Therapeutic Agents. Issue 6 (16th December 2020) - Choi, Junhee; Hwang, Junsun; Kim, Jin‐young; Choi, Hongsoo
Abstract: Therapeutic agents, such as drugs and cells, play an essential role in virtually every treatment of injury, illness, or disease. However, the conventional practices of drug delivery often result in undesirable side effects caused by drug overdose and off‐target delivery. In the case of cell delivery, the survival rate of the transplanted cells is extremely low and difficulties with the administration route of cells remain a problem. Recently, magnetically actuated microrobots have started offering unique opportunities in targeted therapeutic delivery due to their tiny size and ability to access hard‐to‐reach lesions in a minimally invasive manner; considerable advances in this regard have been made over the past decade. Here, recent progress in magnetically actuated microrobots, developed for targeted drug/cell delivery, is presented, with a focus on their design features and mechanisms for controlled therapeutic release. Additionally, the practical challenges faced by the microrobots, and future research directions toward the swift bench‐to‐bedside translation of the microrobots are addressed. Abstract : This work reviews recent progress in magnetically controlled medical microrobots developed for targeted delivery of therapeutic agents, such as drugs and cells, with special emphasis on various types of microrobot designs and strategies for controlling drug/cell release. Additionally, practical challenges and future research directions toward the clinical translation of the microrobots are addressed.